The Principle of Reciprocity in Contemporary Court Decisions: Analysis of Qirā'ah Mubādalah in Divorce Decisions of the Surabaya Religious High Court - Ma'shum, Ali; Yustafad; Fatmah; Nailal Muna; Mohammad Rafli; Muhammad Khowarizmi (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Purpose – The purpose of this study is to analyze contemporary judges' considerations in divorce case rulings at the Surabaya Religious High Court and to examine the principle of reciprocity in the Qirā'ah mubādalah theory. Alimony rulings are not based on the status of the father (male) or the mother (female), but rather on who is considered more capable of fulfilling it. Method - The method used was library research by reviewing the divorce decision of the Surabaya Religious High Court in case No. 217/Pdt.G/2021/PTA.Sby. The analysis was carried out using the concept of Qirā’ah mubādalah theory. Findings – The results of the study show that the judge's considerations were not only focused on normative aspects, but also on the socio-economic context of the parties and the correction of procedural errors at the first level. The revocation of māḍiyah income and the adjustment of ḥaḍānah income reflect situational justice in accordance with Q.S. At-ṭalāq. The principle of Qirā'ah mubādalah in the Surabaya Religious High Court (PTA) decision can be seen from the placement of men and women as equal subjects. The adjustment of livelihoods reflects mutual and relational justice, and shows that mubādalah values can be integrated into formal law in a fair and legitimate manner. Research implications and limitations – The limitation of this paper is that it does not present many court decisions on divorce cases as comparative data for this decision. Originality – The study is original in applying Qirā’ah mubādalah to court decision analysis.